Semantics of multisampling systems. (2016) - Barros, Fernando
We present the semantics of the continuous flow system specification (CFSS). CFSS is a modular formalism able to describe hierarchical sampling-based systems with a time-varying topology. CFSS introduces the concept of multisampling to achieve a description of continuous signals on digital computers. Sampling is treated as a first order concept being explicitly supported. Traditional discrete time machines operate at the same rate simplifying the semantics of their interconnection. However, complex systems require machines to specify their sampling rate independently, making their coordination a challenging problem. The CFSS formalism enables sampling to change over time and from component to component, making CFSS a framework for representing multisampling systems. The ability to join machines with different sampling periods is enabled by a novel representation of continuous systems based on digital computers. We illustrate multisampling in the context of a temperature control system that uses independent sampling rates to represent a digital controller and a numerical solver. We also illustrate the ability of CFSS to represent models with a dynamic topology.